An electrochromic material capable of monitoring battery health, preparation method and application thereof

By preparing electrochromic materials and utilizing the color changes caused by light or electricity, the problem of rapid, efficient and continuous leakage detection of lithium-ion soft-pack batteries is solved, and the efficiency of automated production is improved.

CN116987496BActive Publication Date: 2025-09-30ZHEJIANG TONY ELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310962369.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-09-30
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

Existing technologies are unable to quickly and efficiently monitor and detect leakage in lithium-ion soft-pack batteries. Automated testing is risky, time-consuming, and labor-intensive, and there is a lack of continuous monitoring materials.

Method used

Electrochromic materials are prepared using ethoxylated bisphenol A dimethacrylate, antioxidants, photoinitiators and electrochromic polymers (such as metal complexes of pyridine derivatives). Continuous monitoring of battery leakage is achieved through color changes under light or power supply, and a protective film is prepared for soft-pack lithium batteries.

Benefits of technology

It realizes continuous, rapid and efficient detection of lithium-ion soft-pack battery leakage, reduces the risk of automated production and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004371956730000021
    Figure BDA0004371956730000021
  • Figure BDA0004371956730000031
    Figure BDA0004371956730000031
Patent Text Reader

Abstract

The present invention provides an electrochromic material, preparation method, and application for monitoring battery health. Taking the total mass fraction as 100%, the electrochromic material comprises ethoxylated bisphenol A dimethacrylate, tripropylene glycol diacrylate, isobornyl methacrylate, 4-diphenylmethanol methacrylate, 4-acryloylmorpholine, an antioxidant, a photoinitiator, and an electrochromic polymer, wherein the electrochromic polymer is a metal complex of a pyridine derivative. The electrochromic polymer provided by the present invention can rapidly react under the action of light or electricity, causing the color of the material to change from transparent to colored. This allows for continuous monitoring of battery leakage, enabling timely detection of battery leakage problems through electrochromism and prompt replacement of problematic battery modules, thereby facilitating maintenance and servicing of battery equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery safety technology, and in particular to an electrochromic material capable of monitoring battery health, a preparation method and applications thereof. Background Art

[0002] In recent years, with the continuous advancement of lithium-ion battery storage capacity and production technology, lithium-ion batteries have become the primary energy storage device for electronic products and electric vehicles. Accordingly, with the significant increase in usage scenarios and usage volume, the requirements for lithium-ion battery safety performance during production and use are increasing. As electric vehicles demand ever-increasing battery energy density, the requirements for lithium-ion battery protective casings are becoming increasingly stringent, especially for soft-pack lithium batteries.

[0003] When testing lithium-ion protective casings, leakage detection of the battery itself is particularly important. As energy storage devices, leakage in lithium-ion batteries can lead to safety hazards such as overheating, fire, and electric shock. During the battery production process, small localized leakage currents are inevitable, but the safety hazards caused by leakage increase with battery use. Therefore, frequent leakage detection is often required during the use of lithium-ion soft-pack batteries, seriously hindering the improvement of automated production efficiency.

[0004] Currently, leakage detection for lithium-ion soft-pack batteries typically uses an insulation resistance tester to measure the resistance of the insulation layer between the tab and the aluminum foil in the aluminum-plastic film. A low resistance indicates leakage. However, because the metal probe is made of rigid metal, automated testing carries the risk of punctures and cannot directly determine whether the battery is leaking.

[0005] Currently, battery leakage is detected at a specific point in time, lacking long-term monitoring and detection. Existing technologies have also proposed some solutions to solve the above problem, such as:

[0006] Patent CN 207851195 U uses on-site X-ray testing, using X-ray penetration to examine the insulation of the heat seal. This inspection is performed directly after the heat seal is completed. Products that pass the inspection proceed to the next production process; those that fail are eliminated. However, this method only allows for a single-point test on the equipment, detecting only relatively obvious heat seal defects.

[0007] Patent CN 109193052 A maintains an insulation resistance tester permanently connected to the battery pack to ensure continuous testing. Due to limitations in the testing equipment, manual on / off testing is required each time. While the basic principle is the same as conventional production testing, the tester is simply installed on the battery system for a long period of time, rather than providing continuous monitoring. This is also time-consuming and labor-intensive.

[0008] In patent CN 204474570 U, the electrochromic material is simply dispersed into the adhesive layer of the double-sided tape. Although this method can achieve continuous leakage detection, it is difficult to use on soft-pack batteries.

[0009] As mentioned above, the existing technology is still unable to quickly and efficiently determine the leakage problem of lithium batteries, and there is still a lack of materials and components that can effectively detect the leakage of soft-pack batteries. Summary of the Invention

[0010] Purpose of the invention: The purpose of the present invention is to provide an electrochromic material, preparation method and application thereof that can monitor battery health. It is expected that it can be applied to soft-pack lithium batteries, and can continuously, quickly and efficiently determine whether the battery is leaking and transmit leakage information, thereby realizing the automation of leakage detection.

[0011] The technical solution of the present invention:

[0012] An electrochromic material for monitoring battery health, comprising:

[0013]

[0014] In some embodiments, the ethoxylated bisphenol A dimethacrylate is selected from one or more of BPA2EODMA, BPA10EODMA, BPA20EODMA and BPA30EODMA; preferably, the ethoxylated bisphenol A dimethacrylate is a mixture of BPA10EODMA and BPA20EODMA; more preferably, the ethoxylated bisphenol A dimethacrylate is a mixture of BPA10EODMA and BPA20EODMA in a mass ratio of 20-40:5-10.

[0015] In some embodiments, the antioxidant is selected from one or more combinations of antioxidants 1076, 168, and 1010.

[0016] In some embodiments, the photoinitiator is selected from one or more combinations of photoinitiator 184, photoinitiator TPO, and photoinitiator BDK.

[0017] In some embodiments, the electrochromic polymer is a complex of a pyridine derivative and a metal.

[0018] In some embodiments, the metal is any one of Fe and Co.

[0019] In some embodiments, the structural formula of the pyridine derivative is as shown in Formula I:

[0020]

[0021] Wherein R can be selected from any one of -H, -CH3, -F, -Cl, and -Br.

[0022] In some embodiments, the method for preparing the pyridine derivative comprises:

[0023] S1: Dissolve sodium hydroxide in anhydrous ethanol, add it to the reactor, and continue stirring;

[0024] S2: Add 4-formylphenylboronic acid and 1-(pyridin-2-yl)ethanone to the reactor, and react after the addition is completed;

[0025] S3: Add ammonia water to the above reaction system, raise the temperature to ethanol reflux, and continue the reaction;

[0026] S4: After the reaction is completed, the solvent is removed by distillation, and the intermediate is separated and collected by fine column separation;

[0027] S5: putting the above intermediate, sodium bicarbonate and p-dibromobenzene into a reactor, adding a solvent, and heating to reflux to react;

[0028] S6: After the reaction is completed, the solvent is distilled and the product is collected by fine column separation to obtain the pyridine derivative represented by formula I.

[0029] In some embodiments, the molar ratio of the intermediate, sodium bicarbonate, and p-dibromobenzene added is 1:4-6:0.1-1.

[0030] In some embodiments, the method for preparing the electrochromic polymer comprises:

[0031] The pyridine derivative, ferrous chloride, and solvent are uniformly mixed and heated to react; after the reaction, the product is filtered, washed, and separated and collected by a fine column to obtain the electrochromic polymer; the pyridine derivative is complexed with a metal to form a metal complex macromolecular polymer, which can effectively improve the color change effect of ferrous chloride and cobalt, and can quickly respond to leakage phenomena and emit a signal; the reaction principle of the complexation is as follows (for example only), where n is a positive integer:

[0032]

[0033] In some embodiments, the reaction temperature of the heating reaction is 100-120° C., and the reaction time is 18-24 hours.

[0034] In another aspect, the present application provides a method for preparing the electrochromic material capable of monitoring battery health, which specifically comprises:

[0035] Ethoxylated bisphenol A dimethacrylate, tripropylene glycol diacrylate, isobornyl methacrylate, 4-biphenylmethanol methacrylate, 4-acryloylmorpholine, an antioxidant, a photoinitiator and an electrochromic polymer are weighed and mixed according to a mass ratio to obtain the electrochromic material capable of monitoring battery health.

[0036] On the other hand, the present application provides a protective film that can monitor battery health, and the protective film comprises, from top to bottom, a pressure-sensitive adhesive, an ITO film, an electrochromic layer, and a PET layer; the electrochromic layer is obtained by coating and curing the above-mentioned electrochromic material that can monitor battery health.

[0037] In some embodiments, the electrochromic layer has a thickness of 19-23 μm.

[0038] In some embodiments, the pressure-sensitive adhesive is selected from a combination of one or more of DURO-TAK 129A, DURO-TAK 3768, DURO-TAK 1093, DURO-TAK 1099, or DURO-TAK 1154.

[0039] Beneficial effects:

[0040] The electrochromic polymer provided by the present invention is a metal complex of a pyridine derivative, which is a complex capable of electrochromism. It can react rapidly under the action of light or electricity, causing the valence state of the metal to change, thereby causing the color of the material to change from transparent to colored. Based on the electrochromic complex, the present invention also provides an electrochromic material. When the electrochromic material is applied to battery soft packaging, the leakage of the battery can be continuously monitored. The battery leakage problem can be discovered in time through electrochromism, and the problematic battery module can be replaced in time, thereby facilitating the maintenance and care of the battery equipment. DETAILED DESCRIPTION

[0041] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples are illustrative of the present invention and are intended only to illustrate the present invention and are not intended to limit the present invention. Other combinations and various modifications within the scope of the present invention may be made without departing from the spirit or scope of the present invention.

[0042] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure. The CAS number of the 1-(pyridin-2-yl)ethanone is 1122-62-9.

[0043] Preparation of pyridine derivatives

[0044] 10 g of sodium hydroxide and 200 ml of anhydrous ethanol were added to a reactor and stirred continuously to mix evenly; 1.49 g of 4-formylphenylboronic acid and 3.63 (0.03 mol) of 1-(pyridin-2-yl)ethanone were added to the reactor, and the reaction was carried out at 20° C. for 24 hours after the addition was completed; 100 ml of ammonia water was added after the reaction was completed, the temperature was raised to ethanol reflux, and the reaction was continued for 20 hours; after the reaction was completed, the ethanol and water were distilled off, and the mixture was finely separated and collected by column to obtain an intermediate; 3.53 g of the above intermediate, 5 g of sodium bicarbonate and 1.175 g of p-dibromobenzene were added to a reactor, 600 ml of a mixed solvent (toluene: tetrahydrofuran: water = 1:1:1) was added, the temperature was raised to reflux and the reaction was completed; after the reaction was completed, the solvent was distilled off, and the product was finely separated and collected by column.

[0045] Mass spectrometry data of the product: The obtained product was analyzed by LC-MS, and the m / z of the product was 692.27 (100.0%), 693.27 (54.5%), 694.28 (14.6%), and 695.28 (2.5%), confirming that the compound represented by formula I-1 was successfully obtained.

[0046]

[0047] Preparation of electrochromic polymer 1

[0048] 6.92 g of the compound represented by Formula I-1 and 1.26 g of ferrous chloride were added to 100 ml of ethylene glycol diether and reacted at 110°C for 24 hours. After the reaction, the product was filtered, and the resulting filter cake was rinsed three times with methanol and three times with n-hexane. After rinsing, the filter cake was filtered and collected, and the product was analyzed by fine column analysis to obtain electrochromic polymer 1.

[0049] Preparation of electrochromic polymer 2

[0050] 6.92 g of the compound represented by Formula I-1 and 2.38 g of cobalt chloride were added to 100 ml of ethylene glycol diether and reacted at 110°C for 24 hours. After the reaction, the product was filtered, and the resulting filter cake was rinsed three times with methanol and three times with n-hexane. After rinsing, the filter cake was filtered and collected, and the product was analyzed by fine column analysis to obtain electrochromic polymer 2.

[0051] Examples 1-4

[0052] Ethoxylated bisphenol A dimethacrylate, tripropylene glycol diacrylate, isobornyl methacrylate, 4-biphenylmethanol methacrylate, 4-acryloylmorpholine, antioxidant 1010, photoinitiator 184, and an electrochromic polymer were weighed and mixed according to a mass ratio to obtain the electrochromic material capable of monitoring battery health. The specific addition amounts are shown in Table 1:

[0053] Table 1 Addition amount of each raw material in Examples 1-4

[0054]

[0055]

[0056] Comparative Example 1

[0057] The preparation method of electrochromic material 5 is similar to that of Example 1, except that ferrous chloride is added instead of the electrochromic polymer. The remaining preparation steps are the same as those of Example 1. The obtained product is recorded as electrochromic material 5.

[0058] Comparative Example 2

[0059] The preparation method of electrochromic material 6 is similar to that of Example 1, except that a pyridine derivative is added instead of the electrochromic polymer. The remaining preparation steps are the same as those of Example 1. The obtained product is designated as electrochromic material 6.

[0060] Comparative Example 3

[0061] 6.24 g of 4,7-dimethyl-1,10-phenanthroline and 1.26 g of ferrous chloride were added to 100 ml of ethylene glycol diether and reacted at 110°C for 24 hours. After the reaction, the product was filtered, and the resulting filter cake was rinsed three times with methanol and three times with n-hexane. After rinsing, the filter cake was filtered and collected. The product was analyzed by fine column analysis to obtain electrochromic material 7.

[0062] A 23 μm thick PET (Lucky FP612-50) substrate was ultrasonically cleaned with acetone, ethanol, and deionized water for 20 minutes, then secured to a substrate tray with high-temperature tape. The electrochromic materials were screen-printed onto the substrate surface to prepare a 30 μm thick electrochromic layer. The electrochromic layer was then cured at 80°C for 2 hours to solidify the electrochromic material. A 20 nm thick ITO layer was obtained by magnetron sputtering using ITO as the target, argon and oxygen as the sputtering gases, a total pressure of 2.0 Pa, an oxygen partial pressure of 6%, a target-to-substrate distance of 15 cm, an initial substrate temperature of room temperature, a DC power supply of 70 W, and a deposition time of 30 minutes. A 30 μm thick pressure-sensitive adhesive (DUR0-TAK 129A) was evenly applied over the ITO layer by screen printing, and the materials were heat-pressed at 100°C. Finally, the surface of the protective film was simply cleaned with ethanol to obtain protective films 1-7, and the following tests were performed:

[0063] Protective films 1-7 were tested in an N2 / H2 (molar ratio 9:1) atmosphere. A coloring voltage of +2V was applied, and the coloring time was recorded. A coloring voltage of +2V was applied for 2 minutes, followed by a fading voltage of -2V for 4 minutes, with each cycle consisting of 20,000 cycles. The coloring time of the protective films was again recorded. The color change was observed and the color change time was recorded. The data obtained are shown in Table 2.

[0064] Table 2 Data results of protective films 1-7 tests

[0065]

[0066]

[0067] As can be seen from the table above, the material of the electrochromic layer significantly influences the coloration response time. The pyridine derivatives provided by this invention can effectively increase the response speed of ferrous and cobalt, enabling the product to emit signals quickly. The technical means of this invention significantly improve the electrochromic response speed of the product, enabling a rapid reaction to change the material's color from transparent to colored, facilitating maintenance and repair of the battery device.

[0068] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. An electrochromic material capable of monitoring battery health, characterized in that: The total mass fraction is 100%, including: Ethoxylated bisphenol A dimethacrylate 30-50%; Tripropylene glycol diacrylate 10-30%; Isobornyl methacrylate 20-40%; 4-Biphenylmethanol methacrylate 5-10%; 4-Acryloylmorpholine 5-10%; Antioxidant 0.1-1%; Photoinitiator 1-3%; Electrochromic polymer 0.01-1%; The electrochromic polymer is a complex of a pyridine derivative and a metal; The metal is any one of Fe and Co; The structure of the pyridine derivative is shown in Formula I: Formula I.

2. The electrochromic material capable of monitoring battery health according to claim 1, characterized in that: The preparation method of the pyridine derivative comprises: S1: Dissolve sodium hydroxide in anhydrous ethanol, add it to the reactor, and continue stirring; S2: Add 4-formylphenylboronic acid and 1-(pyridin-2-yl)ethanone to the reactor, and react after the addition is completed; S3: Add ammonia water to the above reaction system, raise the temperature to ethanol reflux, and continue the reaction; S4: After the reaction is completed, the solvent is removed by distillation, and the intermediate is separated and collected by fine column separation; S5: putting the above intermediate, sodium bicarbonate and p-dibromobenzene into a reactor, adding a solvent, and heating to reflux to react; S6: After the reaction is completed, the solvent is distilled and the product is collected by fine column separation to obtain the pyridine derivative represented by formula I.

3. The electrochromic material capable of monitoring battery health according to claim 2, characterized in that: The added molar ratio of the intermediate, sodium bicarbonate and p-dibromobenzene is 1:4-6:0.1-1.

4. The electrochromic material capable of monitoring battery health according to claim 1, wherein: The preparation method of the electrochromic polymer comprises: The pyridine derivative, ferrous chloride and solvent are mixed evenly and heated to react; after the reaction is completed, the product is filtered, washed, and separated and collected by a fine column to obtain the electrochromic polymer.

5. The electrochromic material capable of monitoring battery health according to claim 4, characterized in that: The reaction temperature of the heating reaction is 100-120° C., and the reaction time is 18-24 hours.

6. The method for preparing the electrochromic material capable of monitoring battery health according to any one of claims 1 to 5, characterized in that: include: Ethoxylated bisphenol A dimethacrylate, tripropylene glycol diacrylate, isobornyl methacrylate, 4-biphenylmethanol methacrylate, 4-acryloylmorpholine, an antioxidant, a photoinitiator and an electrochromic polymer are weighed according to a mass ratio and mixed uniformly to obtain the electrochromic material capable of monitoring battery health.

7. A protective film capable of monitoring battery health, characterized in that: The protective film comprises, from top to bottom, a pressure-sensitive adhesive, an ITO film, an electrochromic layer, and a PET layer; the electrochromic layer is obtained by coating and curing the electrochromic material capable of monitoring battery health as described in any one of claims 1 to 6.

8. The protective film capable of monitoring battery health according to claim 7, characterized in that: The thickness of the electrochromic layer is 19-23 μm.

Citation Information

Patent Citations

  • An automotive battery with electric leakage detection

    CN109193052A

  • Electrochromic transparent double-sided adhesive tape

    CN204474570U

  • Lithium cell leakage detection device

    CN207851195U

  • Alkyl chain bridged terpyridyl iron coordination polymer electrochromic material

    CN112250881A

  • Novel metallo super molecule polymer-containing composition, and highly efficient manufacturing method of metallo super molecule polymer-containing composition using microwave

    JP2018145244A